2021
DOI: 10.5539/gjhs.v13n3p37
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Anemia among Adolescent Girls: A School-Based Survey in Central Java, Indonesia

Abstract: Squamous cancer of the oesophagus has been, for almost a century, a major cause of morbidity and mortality in East and Southern Africa, and has been referred to as endemic in many high-incidence regions. Uncertainty about aetiology has inhibited effective preventive initiatives. The aims of this study are to assess why some African regions and countries have a very high incidence of oesophageal cancer; to assess evidence-based associations and risk factors for population susceptibility and for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…National Health Survey data revealed that the prevalence of anemia in Indonesia at the age of 5-14 years was 26,4% and 15-24 years was 18,4%; 32% in 2013 increased for ages 5-14 years to 26,8% and 32% in 2018 (Kemenkes RI, 2013;Kemenkes RI, 2018). Several studies related to the prevalence of anemia in adolescent girls in Indonesia show that the prevalence of anemia is still above 20% (ranging from 21 to 45%) (Permatasari et al, 2020;Agustina et al, 2020;Masfiah et al, 2021;Rahfiludin et al, 2021). The prevalence of anemia is included in the moderate category of public health problems, so it requires special attention (WHO, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…National Health Survey data revealed that the prevalence of anemia in Indonesia at the age of 5-14 years was 26,4% and 15-24 years was 18,4%; 32% in 2013 increased for ages 5-14 years to 26,8% and 32% in 2018 (Kemenkes RI, 2013;Kemenkes RI, 2018). Several studies related to the prevalence of anemia in adolescent girls in Indonesia show that the prevalence of anemia is still above 20% (ranging from 21 to 45%) (Permatasari et al, 2020;Agustina et al, 2020;Masfiah et al, 2021;Rahfiludin et al, 2021). The prevalence of anemia is included in the moderate category of public health problems, so it requires special attention (WHO, 2011).…”
Section: Introductionmentioning
confidence: 99%